KARAKTERISASI PROFIL SENSORI DAN KIMIA DONAT DENGAN PENAMBAHAN TEPUNG RUMPUT LAUT Kappaphycus alvarezii - azis, Muhammad Amirruddiin; Surilayani, Dini; Haryati, Sakinah; Munandar, Aris (Pusat Unggulan Iptek Ketahanan Pangan Universitas Sultan Ageng Tirtayasa, 2023)
Indonesia had become one of the world's main producers of seaweed with most of the species Kappaphycus alvarezii and Gracillaria sp. Donuts are included in the bakery product category. With the addition of seaweed flour in the manufacture of donuts, it is expected to increased the fiber content in the donuts, because seaweed had a relatively high fiber content, so it can improve digestive function. This study aimed to determined the best formulation of the addition of K. alvarezii seaweed flour to donuts. This study used a completely randomized design (CRD) with 2 replications. The treatment in this study was the addition of K. alvarezii seaweed flour which was different with 5 levels namely: 0%, 10%, 20%, 30% and 40%. The quality parameters analyzed were the hedonic test, including colour, aroma, taste and texture. Donuts with the best hedonic test were tested for crude fiber content and proximate tests, namely moisture content, ash content, fat content, protein content, and carbohydrate content. The addition of 10% seaweed powder (D1) was the best treatment with hedonic taste (3.36 ± 0.55), aroma (3.10 ± 0.80), color (3.83 ± 0.79), and texture (4.06 ± 0.63). Based on the chemical properties test, namely crude fiber content (0.14%) and proximate namely water content (25.61%), ash content (2.53%), fat content (15.91%), protein content (2.61%) )%, and carbohydrate content (53.34%). The addition of seaweed powder to donut production affects the hedonic and chemical characteristics of donuts.